2017
DOI: 10.1080/01694243.2017.1381015
|View full text |Cite
|
Sign up to set email alerts
|

Removal of temporary cements following an immediate dentin hybridization approach: a comparison of mechanical and chemical methods for substrate cleaning

Abstract: This study evaluated the microshear bond strength (SBS) of a composite resin cement to a pre-hybridized dentinal substrate exposed to two kinds of temporary materials; the influence of different cleaning techniques was investigated. Dentinal surfaces were conditioned with an etch-and-rinse adhesive system to obtain an immediately-sealed (IDS) layer. Each surface was divided into quadrants and covered (1) with an eugenol-free (NE_Group) or (2) with a resin-based provisional agent (CL_Group). After storage, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“… Nikaido et al 2018 17 Review - - Coating materials have the potential to reinforce sound tooth,leading to the maximum preservation of tooth structures. Augusti et al 2018 47 In vitro Bond strength Investigated the influence of different cleaning techniques (Hand-scaler/Alumina air-abrasion/Glycine powder air-abrasion/D-Limonene chemical solvent) upon microshear bond strength of a composite resin cement (Nexus Universal adhesive luting cement) to a pre-hybridized dentinal substrate (Optibond FL) exposed to two different temporary materials (TempBond NE/TempBond Clear) IDS protected freshly-cut dentin from the adverse effects of temporary materials. Glycine air-abrasion was suggested when a temporary resin cement is adopted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Nikaido et al 2018 17 Review - - Coating materials have the potential to reinforce sound tooth,leading to the maximum preservation of tooth structures. Augusti et al 2018 47 In vitro Bond strength Investigated the influence of different cleaning techniques (Hand-scaler/Alumina air-abrasion/Glycine powder air-abrasion/D-Limonene chemical solvent) upon microshear bond strength of a composite resin cement (Nexus Universal adhesive luting cement) to a pre-hybridized dentinal substrate (Optibond FL) exposed to two different temporary materials (TempBond NE/TempBond Clear) IDS protected freshly-cut dentin from the adverse effects of temporary materials. Glycine air-abrasion was suggested when a temporary resin cement is adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Application of a separating medium combined with spot bonding seems to serve the above-mentioned requirements. Moreover, resin-based temporary cements should be avoided, 47 unless isolation using a water-soluble gel has been applied beforehand. 34…”
Section: Resultsmentioning
confidence: 99%
“…Several researches have evaluated the effect of temporization on dentin with/without resin-coating 9,24,25) . It was revealed that the removal of non-eugenol temporary cement with only the excavator was enough to avoid the reduction in the final bond strength 24,25) . However, cement remnants were observed in the noncoated and resin-coated groups (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of provisional cement has been shown to exert a significant effect on the bond strength of the final restorations. The use of calcium hydroxide and zinc oxide eugenol-free cement has been shown to have little or no effect on bond strength of final restorations as compared to zinc oxide-eugenol and resin-based provisional cements [ [76] , [77] , [78] ].…”
Section: Invito Studiesmentioning
confidence: 99%
“…As provisional cement potentially contaminates the surface of the first layer of the resin adhesive resulting in compromised bond strength, a thorough cleaning of provisional luting cements before final cementation is essential [ [79] , [80] , [81] , [82] ]. Different provisional cement cleaning methods have been suggested which can be categorized as mechanical [ [76] , [77] , [78] , [79] , [80] , [82] , [83] , [84] , [85] , [86] ] chemical [ 78 , 80 , 87 ] and laser [ 80 ] ( Table 4 ). It is important that the cleaning method being used removes all remnants of provisional cement from the surface of the first resin adhesive layer to allow optimal bonding with the second resin adhesive layer that is applied during the final cementation.…”
Section: Invito Studiesmentioning
confidence: 99%